Pengaruh Kualitas Produk, Promosi dan Nilai Pelanggan Terhadap Keputusan Pembelian di PT Weedo Niaga Global - Mahatta Mahatta; Heryenzus Heryenzus (eCo-Buss, 2023)
With the advent of growing globalization, the business world is booming, leading to the fact that they all have strong competitiveness, so that without them knowing it, they can do everything from entrepreneurs to profits achieved through power struggles. competition from competitors that appear in the global business market. The benefits and objectives of this study are to determine the effect of product quality, promotion and customer value on purchasing decisions at PT Weedo Niaga Global simultaneously. This research uses descriptive research through a quantitative approach. The application program used namely SPSS version 26. The sample obtained from the simple random sampling technique was 105 respondents. The data collection process uses the google form in the form of a questionnaire and has been processed using SPSS. The results that have been tested through statistical tests on the variables of product quality, promotion and customer value are data that show normal distribution data, independent variables have no ties to the absence of multicollinearity and heteroscedasticity. Test results there are, among others, the coefficient of determination as much as 77.9%, the f test proves the value of 52.133> 2.69 with sig 0.000 <0.05 that simultaneous occurrence between product quality, promotion and customer value has a significant effect on purchasing decisions. The t test results from product quality of 2,390 > 1.98326, promotion of 2,862 > 1.98326 and customer value of 4,428 > 1.98326. Therefore all t test results include the interpretation of the accepted hypothesis.